Analisis Perubahan Penggunaan Lahan Sawah Menjadi Lahan Terbangun di Kecamatan Gubug Kabupaten Grobogan Tahun 2000-2018 - Ruwanto, Sandi; Banowati, Eva (Geo-Image, 2021)
The Changes from paddy fields to developed land always occur. Changing paddy fields that are notin accordance with the Regional Spatial Plan (RTRW) will cause problems. According to data fromthe Grobogan Regency Agriculture Service, Gubug District has illegally converted rice fields intobuilt-up land. The objectives of this research are: 1) To find out the chaotic pattern of changes in theuse of paddy fields to developed land in the District Gubug 2000-2018. 2) Assessing the dominantfactors causing the conversion of paddy fields to developed land in Gubug District 2000-2018. Datacollection techniques with interviews and questionnaires. The data analysis technique used is nearestneighbor analysis and percentage descriptive. The results of the research in Gubug District showedthat the spatial pattern of changing paddy fields into built-up land was clustered. This clusteringpattern occurs in several villages that are located close to the city center and villages that are locatedadjacent to other sub-districts in Grobogan Regency. The factors that most dominate the causes ofchanging paddy fields to developed land are the factor of low knowledge of the population aboutpermits to change paddy fields to developed land and the factor of land needs for settlements whichcontinues to increase due to the growing population. Perubahan lahan sawah menjadi lahan terbangun setiap tahun selalu terjadi. Berubahnya lahansawah yang tidak sesuai dengan Rencana Tata Ruang Wilayah (RTRW) akan menimbulkanpermasalahan. Menurut Data dari Dinas Pertanian Kabupaten Grobogan, Kecamatan Gubugbanyak terjadi perubahan sawah menjadi lahan terbangun secara ilegal. Tujuan dari penelitian iniadalah: 1) Mengetahui pola keruanagan perubahan penggunaan lahan sawah menjadi lahanterbangun di Kecamatan Gubug Tahun 2000-2018. 2) Mengkaji faktor dominan penyebabperubahan lahan sawah menjadi lahan terbangun di Kecamatan Gubug Tahun 2000-2018. Teknikpengambilan data dengan wawancara dan kuesioner. Teknik analisis data dengan analisis tetanggaterdekat dan deskriptif persentase. Hasil penelitian di Kecamatan Gubug menunjukan polakeruangan perubahan lahan sawah menjadi lahan terbangun adalah mengelompok. Polamengelompok ini terjadi di beberapa desa yang letaknya dekat dengan pusat kota dan desa yangletaknya berbatasan dengan kecamatan lain di Kabupaten Grobogan. Faktor yang palingmendominasi penyebab berubahnya lahan sawah menjadi lahan terbangun yaitu faktor rendahnyapengetahuan penduduk tentang perizinan merubah lahan sawah menjadi lahan terbangun dan faktorkebutuhan lahan untuk permukiman yang terus meningkat dikarenakan jumlah penduduk yangterus bertambah